Explaining the reproduction of illegal drug use control regimes in Japan: the multi-centred governance thesis. Issue 1 (2nd January 2023) - Brewster, David; Edwards, Adam
ABSTRACT: Despite current global trends towards diversification in policy responses to illegal drug use, including growing criticism of the War on Drugs, Japan continues to retain an ardently prohibitive approach. This article explains the reproduction of prohibitionist policies in Japan throughout the post-War period through use of the Multi-Centred Governance (MCG) thesis. This thesis acknowledges the facilitative power of exogenous shocks to the policy process, the causal power of particular policy actors, whilst also emphasising the importance of dispositional power, the rules of meaning and membership that integrate and bind policy actors into rival agendas of crime control, in maintaining policy agendas despite facilitative and agentic pressures for change. In these terms, the MCG provokes discussion of how alleged global trends in crime and control are mediated by a politics of risk and justice, constituted through the interplay of the facilitative, causal and dispositional circuits of power found in particular contexts.